2016
DOI: 10.1039/c6ob00038j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the photophysical properties of 4′-substituted terpyridines – an experimental and theoretical study

Abstract: Several 2,2':6',2''-terpyridines substituted in the 4'-position were synthesized and their photophysical properties were investigated by absorption and photoluminescence spectroscopy in dilute solutions and solid state. The studies confirmed that the absorption and emission wavelengths, fluorescence quantum yields and lifetimes of 1-R(1-16) are strongly structure-related, demonstrating a decisive role of the nature of the substituent in determining the photophysical properties of 4'-functionalized terpyridines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 63 publications
(306 reference statements)
4
32
0
Order By: Relevance
“…The fluorescence of the 2,6‐di(thiazol‐2‐yl)pyridines with the R 5 , R 7 , R 8 , and R 9 substituents appeared in a lower energy region than those observed for the other 2,6‐di(thiazol‐2‐yl)pyridines with substituents with stronger π‐acceptor properties (R 1 , R 2 , R 3 , R 4 , and R 6 ). Compared with the corresponding 4′‐R‐terpy compounds, the reported 2,6‐di(thiazol‐2‐yl)pyridines show higher quantum yields, as presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fluorescence of the 2,6‐di(thiazol‐2‐yl)pyridines with the R 5 , R 7 , R 8 , and R 9 substituents appeared in a lower energy region than those observed for the other 2,6‐di(thiazol‐2‐yl)pyridines with substituents with stronger π‐acceptor properties (R 1 , R 2 , R 3 , R 4 , and R 6 ). Compared with the corresponding 4′‐R‐terpy compounds, the reported 2,6‐di(thiazol‐2‐yl)pyridines show higher quantum yields, as presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…(a) Energy‐level diagram of the calculated IP, EA, and E g values of 2,6‐di(thiazol‐2‐yl)pyridines (black) determined by DPV and compared with the data for the corresponding 2,2′:6′,2′′‐terpyridines (red) . (b) Reductive and (c) oxidative scans of R 8 ‐dtpy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A vast number of derivatives containing carbazole or terpyridine units can be found in the literature, but relatively few reports on compounds carrying both units separated by a π–conjugated system . Therefore, there is room for developing new carbazole‐terpyridine derivatives with enhanced optoelectronic features, also to widen our knowledge on the relationship between the structure and the electronic properties . Our earlier work carried out on this type of molecules showed that the absorption and emission properties of carbazole‐terpyridine dyads can be finely tuned by changing the spacers between the two terminal subunits …”
Section: Introductionmentioning
confidence: 99%